2001
DOI: 10.1074/jbc.m100570200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulatory Role of Sp1 in Metal Responsive Element-mediated Transcriptional Activation

Abstract: Transcription of mammalian metallothionein (MT)genes is activated by heavy metals via multiple copies of a cis-acting DNA element, the metal-responsive element (MRE). Our previous studies have shown that certain MREs of the human MT-IIA gene (MREb, MREc, MREd, and MREf) are less active than the others (MREa, MREe, and MREg). Gel shift analysis of HeLa cell nuclear proteins revealed that whereas the active MREs strongly bind the transcription factor MTF-1 essential for metal regulation, the less active MREs bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…In addition, the molecular interactions between Sp1ID and the corepressors can explain how Sp1 can function as a transcription repressor in certain Sp1-bound promoters (23)(24)(25)(26)(27), even though Sp1 is known to be a transcription activator, in general (Refs. 3-5 and references therein) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the molecular interactions between Sp1ID and the corepressors can explain how Sp1 can function as a transcription repressor in certain Sp1-bound promoters (23)(24)(25)(26)(27), even though Sp1 is known to be a transcription activator, in general (Refs. 3-5 and references therein) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these molecular interactions with the corepressors may constitute a key factor in the transcriptional regulation of the Sp-family, via the modulation of the target GC-box binding of Sp1ZFDBD. Moreover, the molecular interactions occurring between Sp1ID and the corepressors may explain the transcription repression by the Sp1 bound to the enhancer or to the proximal promoter GC-box (23)(24)(25)(26)(27).…”
Section: Sp1zfdbd and Sp1id Can Repress Transcription Once Targeted Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Sp1 is ubiquitously expressed in human tissues serving mainly as an activator of transcription for housekeeping genes and genes involved in growth regulation, but it can also act as a repressor in certain circumstances (Armstrong et al, 1997;Briggs et al, 1986;Dennig et al, 1995;Hagen et al, 1994;Kadonaga et al, 1987;Kwon et al, 1999;Lee et al, 2005;Li et al, 1998;Murata et al, 1994;Ogra et al, 2001;Shou et al, 1998;Suzuki et al, 2000;Zaid et al, 2001). Containing three C2H2 domains, Sp1 binds to the consensus sequence 5'-(G/t)GGGCGG(G/A)(G/A)(C/T)-3' in GC-rich promoters found in many genes (Armstrong et al, 1997;Berg, 1992;Bucher, 1990;Kadonaga and Tjian, 1986).…”
Section: α α α α-Helix Dna Binding Surface: Canonicalmentioning
confidence: 99%
“…34 However, there are several reports that Sp1 serves the unusual role of repressing gene expression and acts as a silencer of gene expression in many cell lines. [35][36][37] Moreover, it was reported that a nuclear protein, p74, interacts directly with the transactivation domain of Sp1 protein and negatively regulates the Sp1- mediated transactivation. 38 These findings suggest that in our present report Sp1 binds gelsolin promoter and directly or indirectly repress expression of gelsolin of human bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%